Προσδιορισμός των ολικών φαινολικών συστατικών και της αντιοξειδωτικής ικανότητας στις φλούδες και στα γίγαρτα του σταφυλιού, στις ποικιλίες Ξυνιστέρι/ Μαραθεύτικο - Τσαέρας, Γιώργος (Τμήμα Γεωπονικών Επιστημών, Βιοτεχνολογίας και Επιστήμης Τροφίμων, Σχολή Γεωτεχνικών Επιστημών και Διαχείρισης Περιβάλλοντος, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2017)
Phenolic compounds belong to the phytochemicals and offer many health benefits to humans by providing protective action against certain diseases such as cancer and heart disease. The protective effect of phenolic compounds is mainly due to their antioxidant capacity. As antioxidants, polyphenols have the ability to neutralize free radicals by trapping them, thus, limiting cell damage and avoiding damage to lipids, proteins, enzymes, carbohydrates and DNA. The aim of the present study is to determine the total phenolic component and the antioxidant capacity of peels and seeds of the grapes of Maratheftiko and Xynisteri varieties. The determination of total phenolic components was carried out by the Folin-Ciocalteu method and antioxidant capacity by the DPPH method on samples of peels and seeds for each variety. Based on the statistical analysis, it was found that the content of total phenolic components and the antioxidant capacity of peel and seeds are different for each variety.
Keywords: Maratheftiko; Xynisteri; Antioxidant capacity; Phenolic ingredients; Μαραθεύτικο; Ξυνιστέρι; Αντιοξειδωτική ικανότητα; Φαινολικά συστατικά